Talent management practices and job performance among academic librarians: a proposed framework / Mohd Noor Hasman Mohd Tumari, Shamila Mohamed Shuhidan and Mohamad Rahimi Mohamad Rosman - Mohd Tumari, Mohd Noor Hasman; Mohamed Shuhidan, Shamila; Mohamad Rosman, Mohamad Rahimi (Faculty of Information Management, 2023)
Talent management practices are an important process for an organisation to maintain and secure excellent staffing for a long time due to sustainable organisation performance. However, in ensuring the preparation of quality and excellent succession staff in development, there are still weaknesses that need to be taken into account by the organisation for that purpose, which include in academic library. Previous studies claimed that among the factors were limited program development related to talent management, the role of libraries and librarianship proficiency, and job insecurity issues. Therefore, this article aims to explore Talent Management Practices (TMP) and Job performance (JP) among Academic librarians (AL) in Malaysia. A proposed framework discovered in this paper is five (5) main areas of TMP namely: job competency (JC), job environment (JE), job reward (JR), job training (JT), and job development (JD). This paper is explored through an analysis of the critically relevant literature and found that the need for talent management development programs, librarian competencies, and job rewards have a relationship in creating important conditions for en-couraging librarians to show good career performance in organisations. It is believed that this paper will provide relevant information on positive work behaviors that will assist libraries and universities in providing effective ser-vices to benefit students and academic staff in academic and research pro-grams.